Business and Professional Income Under the Personal Income Tax - Kahn, C. Harry (Charles Harry), 1921- (Book collections on Project MUSE., 1964)
The author is concerned here with the tax treatment of individuals' income from the sole proprietorships and partnerships in manufacturing, finance, trade, agriculture, and professional practice. Attention is paid to the changing relation between the income from sole proprietorship and partnership and the total income of owners. Appendixes contain explanations of figures and concepts. Originally published in 1964. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.